Androgenic Alopecia: A Comprehensive Literature Review of Epidemiology, Pathophysiology, Diagnosis, and Management - Maudina, Baiq Zaskia; Wahyudi, Reza Rizwandipa; Dzulilmi, Dhaifatu; Salsabila D.P, Septy Rianty; Prameswari, Devi Shanti; Fauzan, Naufal Revaldy; Saithanya G.D, Ni Made; Bramantyo, Rofi; Putri, Alifia Sabira; Rizqi, Amanda Suana; Salsabila, Ruhaniah Najwa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Androgenetic alopecia (AGA) is the most common form of hair loss in men and women, caused by a complex interaction of genetic and hormonal factors, particularly dihydrotestosterone (DHT). This condition is characterized by the miniaturization of hair follicles and changes in hair growth patterns, which affect the physical and psychological aspects of the sufferers. This article is prepared through a literature review from various recent scientific sources discussing the definition, etiology, epidemiology, pathophysiology, clinical manifestations, diagnosis, management, complications, and prognosis of AGA. Androgenetic alopecia (AGA) is triggered by genetic predisposition, follicle sensitivity to dihydrotestosterone (DHT), and supporting factors such as malnutrition, aging, and vascular disorders. The pattern of baldness differs in men and women, assessed using the Hamilton–Norwood or Ludwig scale. Diagnosis is established through history taking, physical examination, and supportive tests. Management includes topical and systemic therapy, supplements, hair transplantation, and low-level laser therapy (LLLT). AGA is also associated with the risk of actinic keratosis, cardiovascular disease, metabolic disorders, and polycystic ovary syndrome (PCOS) in women. AGA is a progressive chronic condition with multifactorial etiology. Early and appropriate management can slow progression and improve the quality of life of patients. Therapy is individualized, tailored to the degree of severity, gender, and patient response to treatment.